2021
DOI: 10.3389/ffgc.2021.630959
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs and Synergies Between Food and Fodder Production and Other Ecosystem Services in an Actively Restored Forest, Natural Forest and an Agroforestry System in Ghana

Abstract: Active restoration of degraded areas with multi-purpose tree species has been proposed as a measure to counter the losses from deforestation and mitigate consequences for local human communities. In a restoration project at a former mining site in Ghana, ecosystem services (ES) proxies in an actively restored forest were compared to a local agroforestry system and a natural forest. The results provide information about trade-offs and synergies between proxies of multiple ES(s). ES proxies were assessed accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Overall, higher seed mass may enhance seedling success [94,95] at the expense of producing fewer seeds per unit of reproductive effort and reducing dispersal capability [96,97]. In a previous study, we also observed a higher biomass of food and fodder trees in the natural forest [44]. Since the size of the seeds in tropical trees is related to fruit size [98], this is probably a pattern resulting from historical selection by the local population that has favoured tree species with specific traits.…”
Section: Ecosystem Type Relationship With Soil Parameters and Functio...supporting
confidence: 53%
See 2 more Smart Citations
“…Overall, higher seed mass may enhance seedling success [94,95] at the expense of producing fewer seeds per unit of reproductive effort and reducing dispersal capability [96,97]. In a previous study, we also observed a higher biomass of food and fodder trees in the natural forest [44]. Since the size of the seeds in tropical trees is related to fruit size [98], this is probably a pattern resulting from historical selection by the local population that has favoured tree species with specific traits.…”
Section: Ecosystem Type Relationship With Soil Parameters and Functio...supporting
confidence: 53%
“…Decomposition (the rate by which nutrients from plant tissues such as leaves are released back into the ecosystem through the activities of detritivores arthropods [55]) was estimated with a standardised method involving the use of tea bags as a proxy [56]. Regulating (control of pests) and supporting (organic matter decomposition) ecosystem services were also estimated using predators and decomposing organism numbers as proxies [44]. Because of its degraded nature, it has been subjected to agroforestry programs (food crops interplant with trees) to supply both food and energy needs as well as environmental benefits to fringe communities.…”
Section: Ecosystem Functions and Multifunctionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Tree heights (the vertical distance from the topmost living or dead part of the tree to the upslope side of the trunk base; Larjavaara and Muller-Landau, 2013) were measured using Nikon Forestry Pro II Laser Rangefinder/ Hypsometer (Nikon, USA). Percentage tree canopy cover and closure of each plot were estimated using the hemispherical photographs technique following Paletto and Tosi (2009) and local tree species richness at each plot was made comparable through rarefaction (Damptey et al, 2021).…”
Section: Samplingmentioning
confidence: 99%
“…Since then, initiatives such as the Millennium Ecosystems Assessment [5] and the Economics of Ecosystems and Biodiversity [23] have contributed to introducing the concept of ES into the political sphere [24,25]. The management of ecosystems involves the balancing of a broad series of conflicting interests, which often implies rivalry in the provision of services in terms of trade-offs [26,27]. Therefore, when managing the natural environment, the assessment of the ES is a tool able to provide useful knowledge for formulating policies and defining strategies based on the knowledge of the ecosystems and the stakeholders involved [28,29].…”
Section: Introductionmentioning
confidence: 99%